(untitled) (Research, Society and Development, 2020)
This study aims to present the process of elaboration and validation of the Instrument of Measurement of Basic Entrepreneurial Knowledge (IMBEK). It consists of a questionnaire, of closed items and dichotomous responses, which measures the understanding of the individual in three aspects of entrepreneurial knowledge: business entrepreneurship, intraentrepreneurship and social entrepreneurship. Initially, 120 items were elaborated, which passed the evaluation of five specialists in the area of Business Administration, Entrepreneurship and Portuguese language. After evaluating the reviewers, 87 of them were recommended for the later stage, a pilot test with 312 high school, technical, undergraduate and graduate students. Subsequently, statistical tests helped to estimate the quantitative validity and reliability of each item. In the end, 57 of them were deleted, obtaining an instrument considered valid and reliable with 30 questions. As results, we can highlight the potential of IMCEB to estimate the level of entrepreneurial knowledge of the delimited target audience, consisting of a tool of theoretical and methodologically based measurement for the different measurement objectives arising from researchers in the area and teachers of disciplines involving entrepreneurship.